PERNIKAHAN HAMIL DI LUAR NIKAH PERSFEKTIF HUKUM ISLAM - Mustopa, Bagas (IAIN Palopo, 2023)
Marriage is part of the dimension of life that is worth worshiping so it is very important. The reality of life in today's society is that there are certain circumstances that make it unavoidable to get pregnant out of wedlock. This research aims to discuss the law of marrying a pregnant woman out of wedlock in Islam, the differences in the rules between the KHI and Islamic Law regarding marriage to a pregnant woman out of wedlock, and the lineage status of children born in an out-of-wedlock pregnant marriage. The results of the research show that according to Imam Hanafi and Syafi'i, marrying a pregnant woman for adultery is permissible for both the man who impregnated her and another man, but both of them have different opinions regarding the permissibility of having sex with her. Imam Hanafi only allows sexual intercourse if the man who marries her commits adultery with her, while Imam Syafi'i allows sexual intercourse with her whether the man who impregnates her or not. Meanwhile, according to Imam Maliki and Hambali, it is not permissible to marry a pregnant woman out of wedlock, whether to a man who impregnated her or not. As for the fate of children born from out-of-wedlock pregnancies, they will be assigned to men who impregnate their mothers before marriage, not men who marry their mothers after pregnancy.